Preparation method of high-temperature-resistant Al2O3-coated SiO2 filler and application of high-temperature-resistant Al2O3-coated SiO2 filler in epoxy packaging

By modifying the core-shell structure filler of the SiO2 shell on the surface of Al2O3, the interface cracking problem of epoxy resin packaging glue at extreme temperatures is solved, and the performance of high temperature resistance and high heat conductivity of packaging materials is improved, which is suitable for packaging of semiconductor integrated circuits.

CN120554987APending Publication Date: 2025-08-29ANQING XINGKAI ELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510780803.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-11
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

Traditional epoxy resin packaging glue is prone to interface cracking and thermal oxygen aging at extreme temperatures, resulting in an increase in the risk of packaging failure and it is difficult to meet the high temperature resistance requirements of high-reliability electronic equipment.

Method used

The preparation method of high temperature resistance Al2O3@SiO2 filler is adopted to modify the SiO2 shell layer on the surface of Al2O3 to build a core-shell structure, enhance the interface compatibility and heat transfer ability of the filler and epoxy resin, and design naphthalene cyclic epoxy resin and linear phenolic resin as high temperature resistance matrix resin materials.

Benefits of technology

It significantly improves the temperature resistance and thermal conductivity of epoxy resin, reduces the probability of interface defects, improves the thermal stress buffering ability and thermal conductivity of the packaging rubber, and enhances the overall high-temperature resistance of the packaging material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005445635490000081
    Figure BDA0005445635490000081
  • Figure HDA0005445635540000011
    Figure HDA0005445635540000011
  • Figure HDA0005445635540000012
    Figure HDA0005445635540000012
Patent Text Reader

Abstract

The invention relates to the technical field of high-temperature-resistant and high-thermal-conductivity epoxy electronic packaging adhesives, discloses a preparation method of a core-shell Al2O3-coated SiO2 filler and application of the core-shell Al2O3-coated SiO2 filler in epoxy packaging, and designs the preparation method of the core-shell structure filler Al2O3-coated SiO2 by chemically modifying the surface of the Al2O3 filler through high-temperature-resistant SiO2. The high-temperature-resistant SiO2 shell layer is modified on the surface of Al2O3, so that the interface wettability between the epoxy resin and the filler is promoted, the binding force between the filler and the epoxy resin is increased, the dispersity and fluidity of EMC are improved, meanwhile, the 175-DEG C bending strength of the epoxy resin is improved, and the high-temperature usability of the epoxy resin is greatly improved. And finally, the core-shell structure Al2O3-coated SiO2 can easily form a heat-conducting path among the filler, the interface and the matrix resin, so that the overall heat-conducting property of the composite material is improved, the low thermal expansion coefficient of the SiO2 shell layer is improved, the thermal stress is buffered, the temperature resistance is improved, and the core-shell structure Al2O3-coated SiO2 can be widely applied to packaging of semiconductor integrated circuits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-temperature resistant epoxy electronic packaging adhesive, and in particular to a synthesis method of high-temperature resistant (Al2O3@SiO2) and research on its application in epoxy electronic packaging. Background Art

[0002] As electronic devices evolve toward higher power density, miniaturization, and higher frequencies, the operating temperatures of their internal components have increased significantly, placing more stringent demands on the high-temperature resistance of electronic packaging materials. Conventional epoxy encapsulants are susceptible to interfacial cracking and thermal oxidative aging at extreme temperatures, increasing the risk of package failure and hindering the development of high-reliability electronic devices. Integrated design of the filler interface modification and the molecular structure of the matrix resin is a key approach to improving the heat resistance of epoxy encapsulants. Summary of the Invention

[0003] Nano-sizing and surface modification technologies for inorganic fillers have shown significant advantages. Alumina (Al2O3) is widely used as a high thermal conductivity filler due to its high thermal conductivity. Silica has outstanding chemical resistance, flexibility, insulation, temperature resistance, and a low thermal expansion coefficient due to its long Si-O bond and high bond energy (443.7 kJ / mol). It can be used as a reinforcing phase for high-temperature-resistant epoxy encapsulation fillers. In order to solve the problems of epoxy resin in poor temperature resistance and poor thermal conductivity, the present invention provides a method for preparing a high-temperature-resistant Al2O3@SiO2 filler, which combines the advantages of both. The specific technical solution is as follows:

[0004] A method for preparing a high-temperature-resistant Al2O3@SiO2 filler, the specific steps are as follows:

[0005] Step 1: Mix ethanol and water and add Al2O 3, Stir to obtain a suspension;

[0006] Step 2: Add polyvinyl alcohol to the suspension of step 1 and stir evenly to obtain solution 2;

[0007] Step 3: Add tetraethoxysilane to solution 2 of step 2 and stir to obtain solution 3; weigh NH4Cl and dissolve it in NaOH alkaline solution, then add it to solution 3 through a constant pressure dropping funnel, stir and react for 24 hours, stop stirring, and let it stand to separate;

[0008] Step 4: Filter and wash with water to remove the remaining TEOS, ammonium chloride and NaOH, and dry for 24 hours to obtain Al2O3@SiO2.

[0009] Preferably, in step 1, the volume ratio of ethanol to water is 1:1, and the mass of aluminum oxide and the volume ratio of ethanol to water are 1:1.

[0010] Preferably, the drying temperature in step 4 is 100°C.

[0011] An epoxy molding compound comprises the following components: 59.3 parts of epoxy resin, 40 parts of phenolic resin, 735 parts of high-temperature resistant filler, 145 parts of crystalline silicon powder, 2 parts of carbon black, 5 parts of coupling agent, 3 parts of wax, 1.7 parts of accelerator, 6 parts of stress modifier and 3 parts of ion capture agent, wherein the high-temperature resistant filler is Al2O3@SiO2 filler prepared by the above method.

[0012] Preferably, the epoxy resin is one or more of bisphenol A epoxy resin, novolac epoxy resin, biphenyl epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, disulfide epoxy resin, and naphthol epoxy resin.

[0013] Preferably, the phenolic resin is one or more of o-methylphenolic resin, phenol formaldehyde type phenolic resin, biphenyl type phenolic resin, and polyaromatic type phenolic resin.

[0014] Preferably, the wax is one or more of brown polyethylene wax, natural palm wax, stearic acid, oxidized polyethylene wax, montanic acid ester, ester wax or polyamide wax.

[0015] Preferably, the accelerator is one or more of an imidazole curing accelerator, an amine curing accelerator, an organic phosphorus curing accelerator, and an acid anhydride curing accelerator.

[0016] Preferably, the coupling agent is one or more of a titanate coupling agent, a siloxane coupling agent and modified derivatives thereof, and the siloxane coupling agent includes a mercapto-type siloxane coupling agent, an amino-type siloxane coupling agent or an epoxy-type siloxane coupling agent.

[0017] Preferably, the stress modifier is one or more of silicone oil, silicone resin, and silicone rubber.

[0018] A method for preparing the above-mentioned epoxy molding compound comprises the following specific steps:

[0019] Epoxy resin, phenolic resin, high thermal conductive filler, crystalline silicon powder, carbon black, coupling agent, wax, accelerator, stress modifier and ion scavenger are weighed according to the above ratio, and the materials are melted and mixed evenly on an open rubber mixer preheated at a temperature of 60-110°C. The evenly mixed materials are removed from the open rubber mixer, naturally cooled, and crushed to obtain powdery materials, which are pre-formed into cake materials to obtain epoxy molding compounds.

[0020] The new Al2O3@SiO2 filler prepared by the present invention constructs the main heat transfer channel with the high thermal conductivity Al2O3@SiO2 core, optimizes the interfacial stress with the low CTE shell, and enhances the compatibility through surface chemical modification. The high thermal conductivity of the Al2O3 core provides the main heat conduction path, while the SiO2 shell realizes the near-field thermal radiation effect by regulating the filler spacing, thereby enhancing the phonon tunneling efficiency. At the same time, although the amorphous structure of SiO2 (thermal conductivity ~1.4W / m·K) is lower than that of Al2O3, its surface energy is closer to that of epoxy resin (~45mJ / m 2 ) can reduce interfacial phonon scattering. The Al2O3 core layer of this filler has excellent thermal conductivity; the low thermal expansion coefficient of the SiO2 shell buffers thermal stress and improves temperature resistance. The filler's surface is rich in silanol groups that participate in the ring-opening reaction of the epoxy resin, improving the overall temperature resistance and mechanical strength of the rubber compound. The matrix resin design uses naphthalene ring epoxy resin and novolac resin as high-temperature resistant matrix resin materials, synergistically enhancing the overall temperature resistance of the epoxy resin material.

[0021] The present invention has the following beneficial effects: To address the interfacial compatibility between low-polarity fillers and matrix resins, the filler surface is chemically modified with SiO2, and a method for preparing a core-shell structured filler Al2O3@SiO2 is designed. This method is simple and efficient. SiO2 is modified on the surface of Al2O3, and the intermolecular force significantly promotes the interfacial wettability between the matrix resin and the filler, increases the bonding strength between the filler and the epoxy resin, improves the dispersibility of the EMC, enhances the fluidity of the EMC, significantly enhances its compatibility with the matrix resin, makes the filler more evenly dispersed, and reduces the probability of interface defect formation. The low thermal expansion coefficient of the SiO2 shell buffers thermal stress and improves temperature resistance. The interface layer constructs an effective heat transfer channel, has a high thermal conductivity and bending strength in the EMC, and also greatly reduces the cost of the overall formulation. It can be widely used in the packaging of semiconductor integrated circuits. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic diagram of the preparation process of the core-shell structured high thermal conductivity filler Al2O3@SiO2.

[0023] Figure 2 These are the colors of Al2O3, Al2O3@30nm SiO2 and Al2O3@180nm SiO2 before modification.

[0024] Figure 3 This is a schematic TEM diagram of unmodified Al2O3 in Example 2.

[0025] Figure 4 This is a TEM schematic diagram of the core-shell structured high thermal conductivity filler Al2O3@30nm SiO2 prepared in Example 2.

[0026] Figure 5 TEM diagram of the core-shell structured high thermal conductivity filler Al2O3@180nm SiO2 prepared in Example 1.

[0027] Figure 6 Schematic diagram of XRD of Al2O3@SiO2, Al2O3@30nm SiO2 and Al2O3@180nm SiO2 in Examples 1 and 2.

[0028] Figure 7 These are the FTIR spectra of Al2O3@SiO2, Al2O3@30nm SiO2, and Al2O3@180nm SiO2 in Examples 1 and 2.

[0029] Figure 8 This is the actual effect diagram of the modified filler formula in EMC (a is the scan of unmodified Al2O3 filler, b is the scan of Al2O3@180nm SiO2 filler). DETAILED DESCRIPTION

[0030] In order to deepen the understanding of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The embodiments are only used to explain the present invention and do not limit the scope of protection.

[0031] Example 1

[0032] Step 1: Prepare a 2L ethanol-water mixture (volume ratio of 1:1). Weigh 2000g of Al2O3 and add it to the mixture. After stirring for half an hour, add 100ml of TEOS and dissolve it completely. Next, dissolve 80g of ammonium chloride in 200ml of sodium hydroxide solution and add it to the above solution. Then, add 10g of polyvinyl alcohol (PVA). Stir at room temperature for 24 hours to chemically modify the Al2O3 surface with SiO2. Ungrafted residual SiO2 and reactants are washed away by filtration and allowed to stand. The mixture is then dried in an oven at 100°C to obtain a highly heat-resistant core-shell Al2O3@30nm SiO2. The mass ratio of TEOS:PVA:ammonium chloride is 94:10:80.

[0033] Step 2, weigh 59.3g naphthalene ring epoxy resin (HP5000), 40g linear phenolic resin (MEHC-7800M), 735g high thermal conductive filler Al2O3@SiO2, 145g crystalline silicon powder (LG03), 2g carbon black (MA-600), 2g coupling agent (KEM014), 3g coupling agent (CG-0187), 2g oxidized polyethylene wax (LICOWAX PED522), 1g stearic acid monoglyceride (MG), 1.7g triphenylphosphine (TPP), 6g epoxy silicone oil, 3g ion capture agent mix, melt and mix uniformly on an open rubber mixer preheated at a temperature of 110°C, remove the mixed material from the open rubber mixer, cool naturally, and crush to obtain a powdery material, which is preformed into a cake material to obtain EMC.

[0034] Example 2

[0035] The difference between Example 2 and Example 1 is that: in step 1, the volume of TEOS is 150 ml, the mass of ammonium chloride is 120 g; the mass of polyvinyl alcohol added is 15 g, and in step 2, the mixture is melt-mixed uniformly on an open rubber mixer preheated at 110° C.

[0036] The specific steps are as follows:

[0037] Step 1: Prepare a 2L mixed solution of ethanol and water (volume ratio 1:1), then weigh 2000g Al2O3 and add it to the Tris buffer solution. After stirring for half an hour, add 100ml TEOS to fully dissolve it. Secondly, dissolve 120g ammonium chloride in 200ml sodium hydroxide alkaline solution and add it to the above solution. After stirring for 24 hours in the room temperature, SiO2 is modified on the surface of Al2O3 through chemical synthesis. The ungrafted residual SiO2 and reactants are washed away by filtration and drying in an oven at 100°C to obtain a highly heat-resistant core-shell structure Al2O3@180nm SiO2.

[0038] Step 2, weigh 59.3g naphthalene ring epoxy resin (HP5000), 40g linear phenolic resin (MEHC-7800M), 735g high thermal conductive filler Al2O3@SiO2, 145g crystalline silicon powder (LG03), 2g carbon black (MA-600), 2g coupling agent (KEM014), 3g coupling agent (CG-0187), 2g oxidized polyethylene wax (LICOWAX PED522), 1g stearic acid monoglyceride (MG), 1.7g triphenylphosphine (TPP), 6g epoxy silicone oil, 3g ion capture agent mix, melt and mix uniformly on an open rubber mixer preheated at 60°C, remove the mixed material from the open rubber mixer, cool naturally, and crush to obtain a powdery material, which is preformed into a cake material to obtain EMC.

[0039] Example 3

[0040] The difference between Example 3 and Example 2 is that:

[0041] In step 2: weigh 61.5g bisphenol A epoxy resin (NPES-901), 42g biphenyl phenolic resin (MEHC-7851SS), 735g high thermal conductivity filler Al2O3@30nm SiO2, 145g crystalline silicon powder (LG03), 2g carbon black (MA-600), 1.5g coupling agent (KEM014), 2.5g coupling agent (CG-0187), 2g oxidized polyethylene wax (LICOWAX PED522), 1g stearic acid monoglyceride (MG), 1.5g triphenylphosphine (TPP), 4g epoxy silicone oil, and 2g ion scavenger, mix them, melt and mix them evenly on an open rubber mixer preheated at 110°C, remove the mixed material from the open rubber mixer, cool it naturally, and crush it to obtain a powdery material, which is preformed into a cake material to obtain EMC.

[0042] Example 4

[0043] The difference between Example 4 and Example 2 is that:

[0044] In step 2: weigh 61.2g biphenyl epoxy resin (BNPE-3501LL), 41.5g o-methylphenolic resin (PF-8011), 735g high thermal conductivity filler Al2O3@30nm SiO2, 145g crystalline silicon powder (LG03), 2g carbon black (MA-600), 1.7g coupling agent (KEM014), 2.5g coupling agent (CG-0187), 2g oxidized polyethylene wax (LICOWAX PED522), 1g stearic acid monoglyceride (MG), 1.4g triphenylphosphine (TPP), 4.7g epoxy silicone oil, and 2g ion scavenger, mix them, melt and mix them evenly on an open rubber mixer preheated at 110°C, remove the mixed material from the open rubber mixer, cool it naturally, and crush it to obtain a powdery material, which is preformed into a cake to obtain EMC.

[0045] Comparative Example 1

[0046] Step 1: Prepare a 4.0 LPH (8 LPH) Tris buffer solution, weigh 1500 g of Al2O3, and add it to the Tris buffer solution. After stirring for half an hour, add 30 g of 3,4,5-trihydroxybenzoic acid (gallic acid, GA) and dissolve it completely. Next, dissolve 30 g of hexamethylenediamine (LDA) in 100 ml of ethanol and add it to the above solution. After stirring for 24 hours at room temperature, poly(trihydroxybenzoic acid-hexamethylenediamine) PGA-LDA is successfully modified on the Al2O3 surface via oxidative polymerization. Ungrafted PGA-LDA is washed off by filtration and then dried in an oven at 100°C to obtain semi-aromatic alumina@poly(trihydroxybenzoic acid-hexamethylenediamine) (semi-aromatic Al2O3@PGA-LMA).

[0047] Step 2: Weigh 59.3g naphthalene ring epoxy resin (HP5000), 40g linear phenolic resin (MEHC-7800M), 735 semi-aromatic filler Al2O3@PGA-LDA, 145g crystalline silicon powder (LG03), 2g carbon black (MA-600), 2g coupling agent (KEM014), 3g coupling agent (CG-0187), 2g oxidized polyethylene wax (LICOWAX PED522), 1g stearic acid monoglyceride (MG), 1.7g triphenylphosphine (TPP), 6g epoxy silicone oil, and 3g ion capture agent, and mix them uniformly on an open rubber mixer preheated at a temperature of 110°C. The mixed material is removed from the open rubber mixer and naturally cooled, crushed to obtain a powdery material, preformed into a cake material, and obtained EMC.

[0048] Comparative Example 2

[0049] The difference between Comparative Example 2 and Example 1 is that the high thermal conductivity filler Al2O3@30nm SiO2 in step 2 is an unmodified SiO2 filler;

[0050] The specific steps are as follows:

[0051] Weigh 59.3g of naphthalene ring epoxy resin (HP5000), 40g of linear phenolic resin (MEHC-7800M), 735g of unmodified SiO2 filler, 145g of crystalline silicon powder (LG03), 2g of carbon black (MA-600), 2g of coupling agent (KEM014), 3g of coupling agent (CG-0187), 2g of oxidized polyethylene wax (LICOWAX PED522), 1g of stearic acid monoglyceride (MG), 1.7g of triphenylphosphine (TPP), 6g of epoxy silicone oil, and 3g of ion capture agent, mix them, melt and mix them evenly on an open rubber mixer preheated at 110°C, remove the evenly mixed materials from the open rubber mixer, cool them naturally, and crush them to obtain a powdery material, which is preformed into a cake material to obtain EMC.

[0052] Comparative Example 3

[0053] The difference between Comparative Example 3 and Example 1 is that the high thermal conductivity filler Al2O3@30nm SiO2 in step 2 is unmodified Al2O3 filler;

[0054] The specific steps are as follows:

[0055] Weigh 59.3g of naphthalene ring epoxy resin (HP5000), 40g of linear phenolic resin (MEHC-7800M), 735g of unmodified Al2O3 filler, 145g of crystalline silicon powder (LG03), 2g of carbon black (MA-600), 2g of coupling agent (KEM014), 3g of coupling agent (CG-0187), 2g of oxidized polyethylene wax (LICOWAX PED522), 1g of stearic acid monoglyceride (MG), 1.7g of triphenylphosphine (TPP), 6g of epoxy silicone oil, and 3g of ion scavenger, mix them, melt and mix them evenly on an open rubber mixer preheated at 110°C, remove the evenly mixed materials from the open rubber mixer, cool them naturally, and crush them to obtain a powdery material, which is preformed into a cake material to obtain EMC.

[0056] Performance Testing

[0057] Test method:

[0058] Infrared spectroscopy: The powder sample was mixed with KBr and pressed into a pellet. The obtained sample was used for infrared testing. Characterization was performed using a German Bruker Tensor Fourier transform infrared spectrometer. Its scanning resolution was 2 cm -1 , scanning range 400~4000cm -1 , scanned 32 times.

[0059] XRD diffraction pattern: The powder sample was placed on a sample table and flattened, and then scanned using an X-ray diffractometer (SmartLab9KW) with a scanning angle of 10-90° and a scanning speed of 5° / min.

[0060] Transmission electron microscopy (TEM): The powder sample was dissolved in water and dispersed with ultrasound for 15 min. A small drop of liquid was placed on the carbon film. Finally, the morphology of the core-shell structured Al2O3@SiO2 nanoparticles was observed using a transmission electron microscope (TEM, Thermo Fisher Talos F200S).

[0061] Spiral Flow Length (SF): This measurement is based on EMMI-1-66, using a mold to measure the spiral flow length. The spiral flow length is measured in cm at a molding press temperature of 175°C, an injection mold clamping pressure of 6.9 MPa, and a curing time of 120 seconds.

[0062] Gel Time (GT): This method is used to determine the curing characteristics and mixing uniformity of epoxy molding compounds. Pour the epoxy molding compound powder onto the center of a 175±2°C hot plate and immediately spread the powder flat with a tongue depressor. The flattened area should be controlled within 5 cm. 2 Start timing from the moment the powder melts. Use a tongue depressor to push the melt at a frequency of 1 time per second. When the melt changes from a fluid to a gel state, it is determined as the end point and the time taken is read. Repeat the same method three times (the difference between the three measured values ​​should not exceed 2 seconds). The gelation time is the average of the three times.

[0063] Flash length: Generally used to indicate the mixing degree of each component in the molding compound. The better the mixing effect, the smaller the flash. It is measured on the molding machine with the flash metal mold. The mold temperature is 175±2℃ and the transmission pressure is 70kg±2kg / cm 2 Take 20±2g of sample powder and pour it into the laminator cavity for molding. After molding for 120 seconds, open the mold and move the mold to the operating table. Flash the mold and measure the length of the overflow from different grooves. The unit is expressed in mm.

[0064] Bending strength modulus: The sample is pressed by a molding machine (the sample size is 80mm long, 10mm wide, and 4mm high). The molding conditions are: the metal mold temperature is 175±2℃, the injection pressure is 70±2kg / cm 2 The molded specimens were post-cured at 175 ± 2°C for 6 hours and then cooled to room temperature. The flexural modulus was then measured using a three-point bending test method on a universal tensile testing machine.

[0065] Thermal conductivity: When preparing the sample, the pressure of the laminator punch is set to 70±2kg / cm 2 The stroke rate of the punch is about 22±3mm / sec, the temperature of the molding machine is 175±2℃, the molding time is 300s, and the molded specimens are baked in an oven at 175±5℃ for 6 hours for post cure, taken out and cooled to room temperature, and then the thermal conductivity of the body is tested using a thermal conductivity meter.

[0066] Reliability testing: First, the components are packaged using a molding machine. The packaged frame is then placed in a constant temperature and humidity chamber at 60°C and 60% humidity for 40 hours. The frame is then removed and analyzed for delamination using an ultrasonic scanning microscope.

[0067] The test results are shown in Table 1:

[0068] Table 1. Physical properties of epoxy resin formulations

[0069]

[0070] In this example, a core-shell structured, highly heat-resistant filler, Al2O3@SiO2, was prepared by polymerization. By varying the feed ratio of TEOS:Al2O3, Al2O3@SiO2 with a particle size of 30 nm and 180 nm were obtained. The relevant physical properties of the formula were then verified by replacing the same ratio in the epoxy resin formula.

[0071] Figure 2 This is the color of Al2O3 before and after modification. The color of Al2O3 before modification is white, and the color of Al2O3@SiO2 after modification is also light white, indicating that a layer of SiO2 is successfully modified on the surface of alumina.

[0072] Figure 3-5 The shell thickness of Al2O3 before and after modification is 1.000 nm. Unmodified Al2O3 has a relatively smooth shell surface, lacking any shell material. SiO2 with varying shell thicknesses can be produced by reacting an alkaline solution of TOES and ammonium chloride. Increasing the TOES addition by 150 ml further increases the shell thickness, reaching approximately 180 nm.

[0073] Figure 6 Infrared spectra of unmodified Al2O3 and Al2O3@SiO2 with different shells prepared in Example 1-2.

[0074] For unmodified Al2O3, at wave number 445 cm -1 There is an obvious Al-O stretching vibration peak at 780 cm -1 The absorption peaks at 820cm-1 correspond to the bending vibration peaks of the Al-O-Al bond. After modification, Al2O3@30nm SiO2 and Al2O3@180nm SiO2, a new peak at 1090cm-1 appears, which is attributed to the vibration absorption peak of Si-O, indicating that the SiO2 shell is successfully bonded to the surface of alumina.

[0075] Figure 7 The XRD diffraction patterns of Al2O3 before and after modification show no significant shift in the diffraction peaks between 0-90°, indicating that the Al2O3 crystal structure has not changed during use. Furthermore, no SiO2 crystal peaks were found between 17-22°, indicating that SiO2 is an amorphous phase with poor crystallization properties.

[0076] It can be seen from the test results in Table 1 that, by comparing Examples 1-2 and Comparative Examples 1, 2, and 3, it is found that since Al2O3@SiO2 is coated on the surface of Al2O3, the alumina in the SiO2 shell has higher temperature resistance than the semi-aromatic PGA-LDA polymer. The improvement in its temperature resistance is mainly due to the long Si-O bond and high bond energy (443.7 kJ / mol), which has outstanding chemical resistance, flexibility, insulation, temperature resistance, and the low thermal expansion coefficient of the SiO2 shell, which buffers thermal stress. Secondly, the surface of the shell SiO2 contains abundant Si-OH bonds, which is conducive to reacting with the epoxy resin, increasing the bonding force between the filler and the epoxy resin, and improving the dispersibility and temperature resistance of the Al2O3 filler in the EMC.

[0077] The thermal expansion coefficient of Al2O3 (α-phase) (CTE: 6-8×10-6 / K) differs significantly from that of SiO2 (CTE: 0.5×10-6 / K). The core-shell structure forms a CTE gradient transition layer, significantly reducing thermal stress at the filler-epoxy interface. During temperature cycling (-40°C to 200°C), the core-shell structure buffers the interface mismatch between the epoxy resin (CTE: 60-80×10-6 / K) and the filler through a gradient CTE, reducing the probability of microcrack initiation and improving the thermal shock resistance of the packaged device. The core-shell structure (Al2O3@SiO2) also optimizes both thermal conductivity and stress buffering capabilities through the synergistic effect of the heterogeneous interface, providing new insights into high-temperature resistance modification of electronic packaging adhesives. Secondly, in terms of the formula design of epoxy resin, naphthalene ring epoxy resin and linear phenolic resin are used as high-temperature resistant matrix resin materials in the embodiment. This material with a rigid benzene ring structure further improves the working temperature range of the epoxy resin, and synergistically enhances the overall thermal conductivity and temperature resistance of the composite material.

[0078] From the analysis of processing flow length and overflow length, Al2O3@180nm SiO2 molding compound is significantly better than unmodified alumina and silica epoxy molding compound, and the fluidity is improved by more than 25%, indicating that the modified EMC has a better processing window; the overflow is reduced from 3.6mm to 0.4mm, indicating that the overall dispersion of the material is better, the mixing is more uniform, and the consistency of the material is high, thereby significantly improving the stratification phenomenon. The most notable feature is that its hardness is significantly improved, and the 175°C high-temperature flexural modulus is also significantly improved. Through comparative examples 1 and 2, the fluidity, thermal conductivity, high-temperature strength and stratification of EMC are significantly improved, thereby confirming the criticality of the preparation in this embodiment to the Al2O3@SiO2 technology with a core-shell structure high thermal conductivity filler.

Claims

1. A method for preparing a high-temperature-resistant Al2O3@SiO2 filler, the specific steps are as follows: Step 1: Mix ethanol and water and add Al2O 3, Stir to obtain a suspension; Step 2: Add polyvinyl alcohol to the suspension of step 1 and stir evenly to obtain solution 2; Step 3: Add tetraethoxysilane to solution 2 of step 2 and stir to obtain solution 3; weigh NH4Cl and dissolve it in NaOH alkaline solution, then add it to solution 3 through a constant pressure dropping funnel, stir and react for 24 hours, stop stirring, and let it stand to separate; Step 4: Filter and wash with water to remove the remaining TEOS, ammonium chloride and NaOH, and dry for 24 hours to obtain Al2O3@SiO2.

2. The method for preparing a high-temperature-resistant Al2O3@SiO2 filler according to claim 1, characterized in that: In the step 1, the volume ratio of ethanol to water is 1:1, and the mass of aluminum oxide and the volume ratio of ethanol to water are 1:

1.

3. The method for preparing a high-temperature-resistant Al2O3@SiO2 filler according to claim 1, characterized in that: The drying temperature in step 4 is 100°C.

4. An epoxy molding compound comprising the following components: 59.3 parts of epoxy resin, 40 parts of phenolic resin, 735 parts of high-temperature resistant filler, 145 parts of crystalline silicon powder, 2 parts of carbon black, 5 parts of coupling agent, 3 parts of wax, 1.7 parts of accelerator, 6 parts of stress modifier and 3 parts of ion scavenger, wherein the high-temperature resistant filler is Al2O3@SiO2 filler prepared by any one of claims 1 to 3.

5. The epoxy molding compound according to claim 4, wherein: The epoxy resin is one or more of bisphenol A epoxy resin, novolac epoxy resin, biphenyl epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, disulfide epoxy resin, and naphthol epoxy resin.

6. The epoxy molding compound according to claim 4, wherein: The phenolic resin is one or more of o-methylphenolic resin, phenol formaldehyde type phenolic resin, biphenyl type phenolic resin and polyaromatic type phenolic resin.

7. The epoxy molding compound according to claim 4, wherein: The wax is one or more of brown polyethylene wax, natural palm wax, stearic acid, oxidized polyethylene wax, montanic acid ester, ester wax or polyamide wax.

8. The epoxy molding compound according to claim 4, wherein: The accelerator is one or more of an imidazole curing accelerator, an amine curing accelerator, an organic phosphorus curing accelerator, and an acid anhydride curing accelerator.

9. The epoxy molding compound according to claim 4, wherein: The coupling agent is one or more of a titanate coupling agent, a siloxane coupling agent and modified derivatives thereof, and the siloxane coupling agent includes a mercapto-type siloxane coupling agent, an amino-type siloxane coupling agent or an epoxy-type siloxane coupling agent.

10. A method for preparing an epoxy molding compound according to any one of claims 4 to 9, comprising the following specific steps: weighing epoxy resin, phenolic resin, high thermal conductive filler, crystalline silicon powder, carbon black, coupling agent, wax, accelerator, stress modifier and ion scavenger according to the ratios in claims 4 to 9, melting and mixing the materials uniformly on an open rubber mixer preheated at a temperature of 60 to 110° C., removing the uniformly mixed materials from the open rubber mixer, cooling them naturally, and crushing them to obtain a powdery material, which is pre-formed into a cake material to obtain the epoxy molding compound.

Citation Information

Cited By

  • Epoxy resin composite material and preparation method thereof

    CN121226964A

  • Packaging material based on epoxy resin composite material and preparation and application thereof

    CN121427249A